Circulating fibroblast growth factor-23 is associated with vascular dysfunction in the community - Mirza, Majd A.I.; Larsson, Anders; Lind, Lars; Larsson, Tobias E. (Atherosclerosis, 2009)
Subjects with chronic kidney disease (CKD) are at higher risk for cardiovascular (CV) disease than the general population. These patients have elevated circulating levels of FGF23, which predict for increased mortality in CKD patients on hemodialysis. Since CV disease is a major cause of death in CKD, we investigated the association between FGF23 and vascular function. We employed a community-based cohort of subjects aged 70, the PIVUS study ( n = 967), to investigate the relation between serum FGF23, endothelium function and arterial stiffness. Higher FGF23 was weakly associated with both impaired endothelium-dependent ( β = −0.08, p < 0.05) and endothelium-independent ( β = −0.08, p < 0.01) vasodilation. The association was stronger in subjects with eGFR ≥ 90 mL/min/1.73 m 2 ( β = −0.19 and β = −0.22, respectively, p < 0.001). In addition, higher FGF23 was associated with increased arterial stiffness exclusively in subjects with an age-adjusted impaired renal function (eGFR < 60 mL/min/1.73m 2) ( β = 0.26, p < 0.001). All associations were independent of gender, biochemical covariates and established CV risk factors. Higher serum FGF23 levels, even within the normal range, are independently associated with impaired vasoreactivity and increased arterial stiffness in the community. Additional studies are required to determine possible direct vascular effects of FGF23 and whether FGF23 is a modifiable CV risk factor.